2016
DOI: 10.1016/j.jcrs.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of the factors contributing to pupillary optic capture after transscleral fixation of posterior chamber intraocular lens for dislocated intraocular lens

Abstract: Neither author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…No pupillary capture was seen in all cases of four-point scleral suture fixation of the Akreos Adapt IOL. In some series, pupillary capture of the IOL optic has occurred in 7.9–14.3% of cases after scleral fixated sutured posterior chamber IOL implantation [ 18 ], but patients with MFS tended to have a higher rate of pupillary capture of the IOL [ 19 ]. IOL pupillary capture is usually transient, but it might cause complications such as pupillary block with secondary glaucoma, pigmentary dispersion glaucoma and iritis as well as refractive change [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…No pupillary capture was seen in all cases of four-point scleral suture fixation of the Akreos Adapt IOL. In some series, pupillary capture of the IOL optic has occurred in 7.9–14.3% of cases after scleral fixated sutured posterior chamber IOL implantation [ 18 ], but patients with MFS tended to have a higher rate of pupillary capture of the IOL [ 19 ]. IOL pupillary capture is usually transient, but it might cause complications such as pupillary block with secondary glaucoma, pigmentary dispersion glaucoma and iritis as well as refractive change [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Thus, patients with floppy iris syndrome, asymmetric lens fixation, or an abnormal anterior chamber depth may be more prone to developing postoperative pupillary capture. 2,4 Patients with a longer anterior chamber depth may have a more posteriorly placed pupil margin in relation to the limbus and thus decreased distance between the scleral-fixated IOL and iris 4 ; in cases with shallow anterior chambers, turbulent fluid mechanics may increase posterior bowing forces and the chance of pupillary capture. 2 Patients with floppy iris syndrome are more prone to posterior bowing of the iris from anterior chamber fluid mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Dong Jin Kang et al have reported that five eyes (7.8%) had pupillary capture after transscleral IOL fixation. Other complications after transscleral fixation were vitreous hemorrhage in 5 eyes (7.8%) and IOP elevation in 8 eyes (12%) [ 11 ]. Besides, suturing of the haptics to the sclera may result in suture erosion, delayed IOL dislocation owing to suture breakage, or suture exposure-induced endophthalmitis [ 4 , 12 ].…”
Section: Discussionmentioning
confidence: 99%